Severity of Intracranial Large Artery Disease Correlates With Cerebral Small Vessel Disease. Issue 1 (19th November 2021) - Wang, Xue‐yang; Lyu, Jin‐hao; Zhang, Sen‐hao; Duan, Cao‐hui; Duan, Qi; Ma, Xiao‐xiao; Zhang, Ting‐yang; Zhang, Jing; Tian, Cheng‐lin; Lou, Xin
Abstract : Background: Small vessel disease (SVD) shares common vascular risk factors with large artery disease (LAD). However, little is known about the relationship between intracranial artery stenosis and SVD burden. Purpose: To investigate whether SVD burden correlates with severity of intracranial LAD. Study Type: Retrospective. Population: Five hundred and sixteen patients with LAD of arterial circulation were enrolled from one hospital, including 384 males (59 ± 11 years) and 132 females (60 ± 12 years). Field Strength/Sequence: 3 T. T1 ‐weighted fast spin echo (T1 W FSE), T2 W FSE, T2 fluid attenuated inversion recovery, diffusion‐weighted imaging, susceptibility‐weight imaging, and time‐of‐flight magnetic resonance angiography. Assessment: The LAD was divided into mild stenosis (<30%), moderate stenosis (30%–69%), and severe stenosis (≥70%). The Standard for Reporting Vascular Changes on Neuroimaging criteria was used to rate the SVD burden according to the level of white matter hyperintensity (WMH), perivascular space (PVS), cerebral microbleed (CMB), and lacunes. Statistical Tests: Lilliefors test, ANOVA, chi‐squared test, Mann–Whitney U test, Wilcoxon signed rank test, Bonferroni test, Spearman's correlation, logistic regression, and Cohen's kappa test. Results: The grade scores for centrum semiovale PVS (CS‐PVS) were positively correlated with the degree of stenosis ( R  = 0.413), whereas the presence of severe basal ganglia PVS (BG‐PVS) was associated with CMB ( R  = 0.508), lacunes ( R  = 0.365), and severe WMH ( R  = 0.478). In multivariate analysis, severe CS‐PVS (adjusted odds ratio [aOR], 3.1; 95% confidence interval [CI], 1.9–4.8) and lacunes (aOR, 2.1; 95% CI, 1.3–3.4) were associated with severe stenosis of LAD. In addition, CS‐PVS was related to severe stenosis in a dose‐dependent manner: when CS‐PVS score was 3 and 4, the aORs of severe stenosis were 1.9 and 7.7, respectively. Data Conclusion: The severity of LAD in anterior circulation is associated with SVD burden, which suggests that different SVD burden may be used for risk stratification in LAD. Evidence Level: 3 Technical Efficacy: Stage 3